2017
DOI: 10.1021/acsphotonics.7b00724
|View full text |Cite
|
Sign up to set email alerts
|

Piezo-phototronic Effect Enhanced Responsivity of Photon Sensor Based on Composition-Tunable Ternary CdSxSe1–x Nanowires

Abstract: The piezotronic effect and piezo-phototronic effect on materials and devices have been widely studied in binary semiconductors. Wide-band ternary semiconductors are a great class of materials with potential application in nano/microdevices, because of their continuously tunable physical properties with composition. Here, we first demonstrate the piezo-photronics effect of ternary wurtzite structured nanowires (NWs), opening an innovative materials system. Single-crystal ternary CdS x Se 1−x (x = 0.85, 0.60, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 49 publications
1
26
0
Order By: Relevance
“…It can be found that the variation of the current upon illumination increases as the applied light intensity increases. The photosensitivity S of the e‐skin can be simply defined asS%=||IdIlInormald×100%in which I d and I 1 represent the outputting triboelectric current in darkness and under illumination, respectively. As shown in Figure d,e against 20, 40, 60, 80, and 100 µW cm −2 illumination, the photosensitivity is 14.0, 19.8, 22.8, 30.2, and 34.3, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It can be found that the variation of the current upon illumination increases as the applied light intensity increases. The photosensitivity S of the e‐skin can be simply defined asS%=||IdIlInormald×100%in which I d and I 1 represent the outputting triboelectric current in darkness and under illumination, respectively. As shown in Figure d,e against 20, 40, 60, 80, and 100 µW cm −2 illumination, the photosensitivity is 14.0, 19.8, 22.8, 30.2, and 34.3, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The piezoelectric properties of III-As and III-P have not received significant attention, despite being known and utilized for electro-mechanical applications [121,122]. The main reasons for that are the lower piezoelectric coefficients, and non-polar technology ([001] and [110] cubic orientations in zinc-blende), prevailing non-nitride III-V bulk electronic and optoelectronic technology [123,5]. Nonetheless, the various nanostructures Vs. bulk distinctions described in Section 3, apply to non-nitride III-Vs as well.…”
Section: Non-nitride Iii-v Nanowiresmentioning
confidence: 99%
“…A brief summary of different ZnO NW structure designs for piezoelectric nanogenerator fabrication to WZ/ZB mixed phase NWs. In a later work, the piezotronic effect was also demonstrated on CdS and CdSe NWs[109,110], and energy harvesting with CdTe NWs[111].…”
mentioning
confidence: 99%
“…The mechanical vibrations of the nanocrystal were recorded by an optical interferometric method, but current-voltage output was not measured. Piezo-phototronic effect enhanced responsivity and influence of piezo-effect on the junction properties of nanosized CdS x Se 1-x single crystal was investigated experimentally and explained theoretically for frequency scale much below piezoresonance [13].…”
Section: Introductionmentioning
confidence: 99%